Ghana: E-commerce in Ejura. - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
ICTs can help farmers to increase their incomes by enabling them to access information on regional market developments and international agricultural know-how.